2014
DOI: 10.1128/aem.03018-13
|View full text |Cite
|
Sign up to set email alerts
|

Association of Clustered Regularly Interspaced Short Palindromic Repeat (CRISPR) Elements with Specific Serotypes and Virulence Potential of Shiga Toxin-Producing Escherichia coli

Abstract: e Shiga toxin-producing Escherichia coli (STEC) strains (n ‫؍‬ 194) representing 43 serotypes and E. coli K-12 were examined for clustered regularly interspaced short palindromic repeat (CRISPR) arrays to study genetic relatedness among STEC serotypes. A subset of the strains (n ‫؍‬ 81) was further analyzed for subtype I-E cas and virulence genes to determine a possible association of CRISPR elements with potential virulence. Four types of CRISPR arrays were identified. CRISPR1 and CRISPR2 were present in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 45 publications
8
26
1
Order By: Relevance
“…Many spacers in the CRISPR1 locus were shared among strains. Similar to previously reported findings, the CRISPR2a locus contributes to a greater diversity between alleles than does CRISPR1 (34,35,43). Indicative of this are the six direct repeats, 40 unique spacers, and six untypeable allele sequences that made up 15 unique CRISPR2a alleles in the O26:H11 bovine strains (8.4% allele diversity; 15 alleles/178 strains) (see Table S2 in the supplemental material).…”
Section: Molecular Markerssupporting
confidence: 70%
“…Many spacers in the CRISPR1 locus were shared among strains. Similar to previously reported findings, the CRISPR2a locus contributes to a greater diversity between alleles than does CRISPR1 (34,35,43). Indicative of this are the six direct repeats, 40 unique spacers, and six untypeable allele sequences that made up 15 unique CRISPR2a alleles in the O26:H11 bovine strains (8.4% allele diversity; 15 alleles/178 strains) (see Table S2 in the supplemental material).…”
Section: Molecular Markerssupporting
confidence: 70%
“…This is not unexpected, providing that most virulence genes are carried by mobile genetic elements which should be targets of a functional CRISPR-mediated adaptive immunity (Toro et al 2014;Garcia-Gutierrez et al 2015).…”
Section: Crispr Type I-ementioning
confidence: 92%
“…1). These two loci are both present in most E. coli strains, except for strains from the B2 group and Shigella (Touchon and Rocha 2010;Toro et al 2014). A smaller array, CRISPR2b (CRISPR2.2 in Diez-Villasenor et al 2010), containing only two spacers, can be found in the same region (Fig.…”
Section: Crispr Type I-ementioning
confidence: 93%
See 1 more Smart Citation
“…As stated above, this H type is more closely related to O157:H7/H than other H types, which usually carry an EHEC plasmid that is partially responsible for its high pathogenicity. Other flagellar H2 STEC isolates (O103:H2 and O45:H2) also were shown to carry EHEC virulence plasmids and, due to previous findings of a close phylogenetic relationship of H types to O types, the presence of plasmids in this serotype could be a further indicator of a close relatedness to other H2 types (39,46,47). Therefore, the O157:H2 serogroup should be investigated further for its pathogenic potential and the possible emergence of another important serotype.…”
Section: Discussionmentioning
confidence: 99%